Influence of Scouring Phenomenon on Slope Stability in Substructure Construction of Cipeles Bridge - Riskia Jordy; Dewi Amalia; Agastyasa Ghea Amarta (Department of Civil Engineering, Politeknik Negeri Bandung, 2024)
Slope stability represents a crucial aspect of terrain integrity, safeguarding against potential landslides and ensuring structural resilience. Instabilities arise primarily from diminished safety margins and landslide occurrences triggered by alterations in slope dimensions or geometry induced by river water scouring. Such scouring processes engender heightened slope steepness, exacerbating vulnerability to failure. Utilizing Finite Element Method (FEM) software, specifically Plaxis 2D Version 22, back calculation analysis, or reverse analysis, offers a robust approach to assess safety factors and collapse patterns resulting from scour-induced alterations. Our investigation reveals a pronounced expansion of slope failure zones attributable to scour phenomena, encompassing both primary and secondary scour instances. Concurrently, there is a discernible reduction in Safety Factor (SF) values and y-displacement magnitudes along the slope, with the most notable declines observed under condition 3 (displacement-y value reaches 79,53 mm). These alterations stem from geometric transformations within the slope, culminating in increased steepness and corresponding destabilization.